Archive Management at Universitas Negeri Semarang - Suminar, Suminar; Wahyudi, Anang Eko; Wijayanti, Dwi Gansar Santi; Maretta, Yoris Adi (Jurnal Penelitian Pendidikan, 2023)
Since October 20, 2022, the Government Regulation of the Republic of Indonesia No. 36 of 2022 concerning the State University of Legal Entity, Semarang State University, has been issued, which was signed directly by the President of the Republic of Indonesia, Ir. Joko Widodo. The management of a legal entity university requires speed and accuracy in processing existing and created archives. Semarang State University, which has transformed from a Public Service Agency University to a State University of Legal Entity, consists of eight Faculties and Postgraduate Programs. Archives management has so far been managed by each processing unit spread across each location of the unit. The processing of these distributed archives is something that really needs to be organized and managed in an orderly, regular and systematic manner. Dynamic archive management and static archives are managed by each unit with models and methods developed by the unit, and with diverse human resources and existing facilities. The fulfillment of archive management which is still decentralized results in the archives stored depending on the facilities and infrastructure owned by each unit. The purpose of this study is to provide a classification of archives managed at each unit level at Semarang State University and used as data for integrated archive management. With the achievement of this data, it is hoped that archive management can be stronger and more agile. The Centralized Model of archive storage in the form of Archives Unit 1 (one) is an effective way to manage and store properly. The renovation of the UPT Archives Building of Semarang State University which was inaugurated by the Chancellor of UNNES on Friday, January 27, 2023 is a momentum to be able to integrate archives throughout UNNES.